Aspects Of Employee’s Motivation In Tourist Services - Constantinescu, Simona Cristina; Dumitrescu, Carmen Simona; Sicoe-Murg, Oana Maria; Chiș, Sabin (Acta Carolus Robertus, 2022)
Employee motivation is "a science" whose role has proven, over time, to be a very important one. Sometimes recruiting employees is easy, but keeping them more difficult. Keeping employees in the company, creating with their help competitive products on the market, keeping the company in the top, depend to a great extent on how the employer/manager understands the importance of motivating the subordinate staff and knows that he must search, discover and apply those motivational techniques that are in line with employees’ expectations. Why the motivation? Because motivation is an essential element in all fields of activity, especially in the tourism industry, where it is a priority coordinate. Motivation comes from within everyone, from the innermost recesses of the human being and is deeply rooted in the desires and needs of man.